2020
DOI: 10.3389/fphar.2020.585487
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Roles of Artemisinin and Its Derivatives in the Treatment of Type 2 Diabetes Mellitus

Abstract: Type 2 diabetes mellitus (T2DM) is a chronic disease that has become a global public health problem. Studies on T2DM prevention and treatment mostly focus on discovering therapeutic drugs. Artemisinin and its derivatives were originally used as antimalarial treatments. In recent years, the roles of artemisinins in T2DM have attracted much attention. Artemisinin treatments not only attenuate insulin resistance and restore islet ß-cell function in T2DM but also have potential therapeutic effects on diabetic comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 264 publications
(373 reference statements)
0
12
0
Order By: Relevance
“…The antimalarials have also been used to treat metabolic diseases. Chloroquine shows antihypertensive, antilipidemic, and hypoglycemic effects (11), while artemisinin and its derivatives have been used in the treatment of type 2 diabetes mellitus (17). Currently, CQ and CHQ are being tested for neurological diseases such as neurosarcoidosis, as well as chronic lymphocytic inflammation with pontine perivascular enhancement responsive to corticosteroids, and primary progressive multiple sclerosis (13).…”
Section: Clinical Applications Of Antimalarial Drugsmentioning
confidence: 99%
“…The antimalarials have also been used to treat metabolic diseases. Chloroquine shows antihypertensive, antilipidemic, and hypoglycemic effects (11), while artemisinin and its derivatives have been used in the treatment of type 2 diabetes mellitus (17). Currently, CQ and CHQ are being tested for neurological diseases such as neurosarcoidosis, as well as chronic lymphocytic inflammation with pontine perivascular enhancement responsive to corticosteroids, and primary progressive multiple sclerosis (13).…”
Section: Clinical Applications Of Antimalarial Drugsmentioning
confidence: 99%
“…For T2DM, the fasting blood glucose (FBG) level, two-hour postprandial glucose (2hPG) level, weight, and waist circumference (WC) were the main indicators ( Jiang et al, 2020 ; Hu et al, 2021 ). HbA1c represents the average blood glucose level in the preceding 3 months and was the main outcome indicator ( Altobelli et al, 2021 ; Kim and Hur, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Bai et al ( 2020 ) revealed the vital role of pH-dependent molecular rearrangement in the activation and activity of artemisinin against cancer. Interestingly, artemisinin and its derivatives may be valuable in treating obesity and diabetes (Shen et al 2020 ; Jiang et al 2020b ). Artemisinin can also ameliorate inflammation by suppressing the process of epithelial-mesenchymal transition and inducing macrophage polarization to the M2 phenotype, which may help treat inflammatory bowel disease in the future (Huai et al 2020 ).…”
Section: Trpcs Agonistsmentioning
confidence: 99%